2005
DOI: 10.1007/s00213-005-2267-6
|View full text |Cite
|
Sign up to set email alerts
|

Neurocircuitry in alcoholism: a substrate of disruption and repair

Abstract: The chronic, excessive consumption of alcohol results in significant modification of selective neural systems of the brain structure, physiology, and function. Quantitative MR structural imaging, diffusion tensor imaging (DTI), and functional MRI (fMRI), together with neuropsychological challenges, have enabled rigorous in vivo characterization of the results of alcoholism on the brain in the human condition. Neuroimaging has also enabled longitudinal study for the examination of alcoholism's dynamic course th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
339
3
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 431 publications
(365 citation statements)
references
References 155 publications
17
339
3
6
Order By: Relevance
“…In our manuscript reporting gambling task impairments in the samples presented here (Fein et al, 2004b), and in a manuscript on cognitive function in these same subjects (Fein et al, in press), we did not find any associations between performance and duration of abstinence. In the cognition paper, we found that AbsAlc were essentially cognitively normal (except for impairments in spatial functioning which had to be interpreted gingerly because it was the only domain with impairment of 9 domains assessed -yet it was among the domains that are most frequently reported to be impaired in alcoholism and drug addiction (Crews et al, 2005;Munro et al, 2000;Oscar-Berman et al, 1997;Sullivan et al, 2002;Sullivan and Pfefferbaum, 2005). Nonetheless, we found no association between SGT performance and spatial processing ability.…”
Section: Discussioncontrasting
confidence: 40%
“…In our manuscript reporting gambling task impairments in the samples presented here (Fein et al, 2004b), and in a manuscript on cognitive function in these same subjects (Fein et al, in press), we did not find any associations between performance and duration of abstinence. In the cognition paper, we found that AbsAlc were essentially cognitively normal (except for impairments in spatial functioning which had to be interpreted gingerly because it was the only domain with impairment of 9 domains assessed -yet it was among the domains that are most frequently reported to be impaired in alcoholism and drug addiction (Crews et al, 2005;Munro et al, 2000;Oscar-Berman et al, 1997;Sullivan et al, 2002;Sullivan and Pfefferbaum, 2005). Nonetheless, we found no association between SGT performance and spatial processing ability.…”
Section: Discussioncontrasting
confidence: 40%
“…(Dreher and Leibfritz, 1999) was introduced as an in vivo method to detect J-coupled resonances with high signal-to-noise ratio (SNR) by using effective homonuclear decoupling. Here, we tested the feasibility of using CT-PRESS optimized for the detection of Glu (Mayer and Spielman, 2005) in the rat to dissociate the biochemical profile of two brain regions affected in alcohol dependence (Koob, 1999;Sullivan and Pfefferbaum, 2005). Based on the hypotheses that the development of alcohol dependence is mediated by basal ganglia circuitry (Koob, 1999), whereas maintenance of alcohol addiction entails changes in frontocerebellar circuitry Sullivan and Pfefferbaum, 2005), we choose to establish baseline levels of major metabolites and neurotransmitters in the basal ganglia and the cerebellum.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of post-mortem brain of long-term alcohol abusers have reported neuronal loss in gray matter and loss of white matter volume (Harper, 2009;Kril and Harper, 1989;Pfefferbaum, 2004;Sullivan and Pfefferbaum, 2005). These effects are less pronounced in motor, temporal, or cingulate cortices, suggesting that alcohol-induced brain damage is likely brain region selective.…”
Section: Proteomic Studies In Human Post-mortem Brainmentioning
confidence: 99%
“…Alcohol has been shown to damage neurons in multiple brain regions, leading to cognitive impairment and other abnormalities of brain function (Harper, 2009;Pfefferbaum, 2004;Sullivan and Pfefferbaum, 2005). The neuronal and behavioral adaptation of the brain to the constant presence of alcohol can lead to severe withdrawal symptoms when alcohol levels suddenly drop.…”
Section: Proteomic Strategies For Discovery Of Therapeutic Targets Ofmentioning
confidence: 99%